The Effects of Head Pose and Face Roundness on Age Progression in Children Faces (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: This paper analyzes the geometric changes in human face during childhood to estimate the related age; cranial changes are used as age-progression features within childhood stage (0-12) years. Infant face is close to the circular shape turning to an ellipse shape over age progression face oval is determined and drawn using face landmarks, were it’s robust against opening mouth, thinness, fatness or face occlusion by hair.Materials and Methods: The experiments depending on two types of face dataset. First one is the standard FG-NET dataset, which was provided with face landmark points numbered from 1 to 68 [14, 15]. Besides, an Internet-based collected data set of (3010) face images extracted from Daily Photo Project.Results: Drawn face ellipse provided set of measures that significantly modeled changes in forehead size and face roundness. Studied age period was between birth and 12 years old. Exaggerated head size at birth provides round face with big forehead, which starts shrinking as age progresses natural face.Conclusion: Face ellipse provided efficient measures and distances to represent face changes along childhood. Comparing with published researches in young-face age estimation, proposed face ellipse recorded encouraging results.